The Research and Realization of Stepping Speed Regulation for Diesel Engine of Diesel Locomotive - LI Wei-bin; BAO Rui (机车电传动)
Speed regulation of stepping motor controlled by 32-bit microprocessor for diesel engine of diesel locomotive was detailed introduced. The problems of the control was studied and solved. Feasibility and practicality of the scheme are fully proved by field test.